The Influence of Instagram Marketing on Purchasing Decisions with Brand Awareness and Brand Image as Mediating Variables (Case Study of Desserthouse By Widia in Trenggalek Regency) - Carissa Maharani; Lina Saptaria (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the influence of marketing through the Instagram platform on Generation Z purchasing decisions, with brand awareness and brand image as mediating variables at Family Business Desserthouse by Widia in Trenggalek Regency. The research method used is a quantitative approach with Partial Least Square–Structural Equation Modeling (PLS-SEM) analysis and involved 125 respondents who are active Instagram users. The results show that marketing through Instagram has a positive and significant influence on brand awareness, brand image, and purchasing decisions. Furthermore, brand awareness is not able to mediate the relationship between Instagram marketing and purchasing decisions, while brand image is proven to be a significant mediating variable between Instagram marketing and purchasing decisions. These results confirm that promotional strategies through attractive and interactive visual content through Instagram are more effective when they are able to form positive perceptions of the brand. The coefficient of determination (R²) value of 0.733 indicates that the variables of Instagram marketing, brand awareness, and brand image together contribute strongly to purchasing decisions. Marketing managers need to design marketing strategies that focus on building a strong brand image through consistent messages, narratives that describe product values, and customer testimonials.